Influence of Cesarean Section Scar on the Mean Pulsatility Index of the Uterine Artery Doppler between 20 and 34 Weeks of Gestation - Peixoto, Alberto Borges; Guimarães, Débora Silva; Maia e Cruz, Letícia; de Oliveira, Maria Laura; Macedo Filho, Saulo da Silva; de Souza, Luiz Ronan Marquez Ferreira; Tonni, Gabriele; Araujo Júnior, Edward (Geburtshilfe und Frauenheilkunde, 2024)
The aim of this study was to assess the influence of the cesarean section scars on the mean pulsatility index (PI) of the uterine artery Doppler between 20 and 34 weeks of gestation. A secondary objective was to assess the association between previous cesarean section and adverse maternal/perinatal outcomes.A retrospective cohort study was conducted with pregnant women who had their deliveries between March 2014 and February 2023. PI of the uterine arteries Doppler was performed transvaginally between 20–24 weeks and transabdominally between 28–34 weeks. The following variables were considered adverse perinatal outcomes: birth weight < 10th percentile for gestational age, preeclampsia, premature birth, placental abruption, perinatal death, postpartum hemorrhage, neonatal intensive care unit (NICU) admission.A total of 479 pregnant women were included in the final statistical analysis, being that 70.6% (338/479) had no (Group I) and 29.4% (141/479) had at least one previous cesarean section (Group II). Pregnant women with a previous cesarean had higher median of mean PI (1.06 vs. 0.97, p = 0.044) and median MoM of mean PI uterine arteries Doppler (1.06 vs. 0.98, p = 0.037) than pregnant women without previous cesarean section at ultrasound 20–24 weeks. Pregnant women with a previous cesarean section had higher median of mean PI (0.77 vs. 0.70, p < 0.001) and mean MoM PI uterine arteries Doppler (1.08 vs. 0.99, p < 0.001) than pregnant women without previous cesarean section at ultrasound 28–34 weeks. Pregnant women with ≥ 2 previous cesarean sections had a higher median of mean PI uterine arteries Doppler than those with no previous cesarean sections (1.19 vs. 0.97, p = 0.036). Group II had a lower risk of postpartum hemorrhage (aPR 0.31, 95% CI 0.13–0.75, p = 0.009) and composite neonatal outcome (aPR 0.66, 95% CI 0.49–0.88, p = 0.006). Group II had a higher risk of APGAR score at the 5th minute < 7 (aPR 0.75, 95% CI 1.49–51.29, p = 0.016).The number of previous cesarean sections had a significant influence on the mean PI uterine arteries Doppler between 20–24 and 28–34 weeks of gestation. Previous cesarean section was an independent predictor of postpartum hemorrhage and APGAR score at the 5th minute < 7. Pregnancy-associated arterial hypertension and number of previous deliveries influenced the risk of composite neonatal outcome, but not the presence of previous cesarean section alone.
Keywords: sonography; uterus; cesarean section scar; uterine artery Doppler; perinatal outcomes; influence